Geven in Nederland 2022 Maatschappelijke betrokkenheid in kaart gebracht - Bekkers, Rene (Geven in Nederland, 2022)
Giving in the Netherlands provides the macro-economic estimates of philanthropy by households, bequests, foundations, corporations and lotteries. The Center for Philanthropic Studies at Vrije Universiteit Amsterdam has conducted the research since 1995. This is the 13th edition, about giving in the year 2020. Giving in the Netherlands 2022 answers the following questions: How generous are the Dutch in their charitable giving? Who gives to which charitable causes? How has giving behavior developed over the past 25 years? In Giving in the Netherlands, we do not only examine financial contributions, but also volunteer service. Giving in the Netherlands contributes to the visibility of the philanthropic sector in the Netherlands. This is important to legitimize an independent and rapidly growing sector. In 2020, the Netherlands gave € 5.6 billion ($ 5.6 billion, £ 4.9 billion) which equals 0.7% of GDP. As a proportion of GDP, the Netherlands gave slightly less in 2020 than in 2018. In addition, 44% of the population was engaged in volunteer work. Corporations and households give most. Together, corporations and households are responsible for almost 80% of all philanthropy in the Netherlands. While, every source has a favorite charitable cause, health received the most in 2020.